Balkan Candidate Countries Running for Fiscal Consolidation: Legal Frameworks vs. Economic Results - Maksimovska Stojkova, Aleksandra; Nesovska Kjoseva, Elena; Stojmenovska, Irena (Comparative Economic Research. Central and Eastern Europe, 2019)
The subject of this paper is four Balkan countries (Albania, Serbia, Macedonia, and Montenegro) that are determined to join the European Union. More particularly, it looks at their work towards accomplishing the political, legal and economic requirements for the EU. Thus, the legislation with the EU Fiscal Compact is the prime focus. Methodologically, the research is based on an assessment of fiscal and monetary legal documents, evaluating the stages of accomplishing the harmonization with the EU’s conditions. Further, cross‑section analyses are made by in putting selected indicators; additionally, the authors compare the four countries’ achievements. The EU’s rigorous fiscal rules are being quietly bypassed, but more frequently by existing member states than the candidate states; this statement is founded on legal and economic arguments, with mathematical estimations. Consequently, the authors question the political courage and financial capacity of the examined countries to cope with the fiscal compact of the superior EU 28 members. The answers are supported with numerous analyses of EU Reports for each country, as well as tables and figures that compare the states’ results and economic achievements vs. EU fiscal consolidation rules. The EU 28 average is givenin addition as a comparison. The conclusion gives across analysis between the four countries and the EU 28 member states, with accompanying argumentation to the main statement about the legal and economic developments of the examined Balkan countries as well as a future prognosis.